2018
DOI: 10.1002/ijc.31624
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of brain metastases: Prioritization of therapeutic targets

Abstract: We sought to compare the tumor profiles of brain metastases from common cancers with those of primary tumors and extracranial metastases in order to identify potential targets and prioritize rational treatment strategies. Tumor samples were collected from both the primary and metastatic sites of nonsmall cell lung cancer, breast cancer and melanoma from patients in locations worldwide, and these were submitted to Caris Life Sciences for tumor multiplatform analysis, including gene sequencing (Sanger and next‐g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 50 publications
(69 reference statements)
4
21
0
Order By: Relevance
“…Furthermore, while NSCLC patients with EGFR mutations had a higher risk of brain metastases, they had better prognosis than those with EGFR wild-type mutations (Hsu et al 2016). In our study, the frequency of EGFR mutation was 36.9% in 130 BM patients, which is consistent with previous finding (Ferguson et al 2018). Moreover, the frequency of EGFR mutation was significantly higher in patients with AA genotype of mLST8:rs26865 than those with AG/GG.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, while NSCLC patients with EGFR mutations had a higher risk of brain metastases, they had better prognosis than those with EGFR wild-type mutations (Hsu et al 2016). In our study, the frequency of EGFR mutation was 36.9% in 130 BM patients, which is consistent with previous finding (Ferguson et al 2018). Moreover, the frequency of EGFR mutation was significantly higher in patients with AA genotype of mLST8:rs26865 than those with AG/GG.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, one study profiled the characteristics of brain metastases from NSCLC and showed that the EGFR mutation rate in BM was 36.3% (Ferguson et al 2018). Furthermore, while NSCLC patients with EGFR mutations had a higher risk of brain metastases, they had better prognosis than those with EGFR wild-type mutations (Hsu et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…24 Ferguson et al reported overexpression of multiple proteins involved in DNA repair in brain metastases across several solid tumor histologies. 25 Balendran et al reported a high rate of BRCA1 or BRCA2 mutations detected in the brain metastases of patients with ovarian cancer. 26 Of interest, platinum agents have demonstrated efficacy against brain metastases across many tumor types, including breast cancer, suggesting vulnerability of brain metastases to DNAdamaging agents.…”
Section: Discussionmentioning
confidence: 99%
“…Our understanding of the brain‐homing process has been rather limited because research focused on brain dissemination has been restricted by the paucity of available preclinical models and human specimens annotated for development of cerebral lesions. The emergence of newer studies of key molecules involved in brain metastasis has added some new insights to our current understanding of the pathogenesis of disease while providing new opportunities for developing brain metastasis–specific therapies …”
Section: Introductionmentioning
confidence: 99%
“…The emergence of newer studies of key molecules involved in brain metastasis has added some new insights to our current understanding of the pathogenesis of disease while providing new opportunities for developing brain metastasis-specific therapies. [8][9][10][11][12][13][14][15][16] Using an integrated clinical and bench-based approach, we previously showed that melanomas that tend to spread, survive, and proliferate in the central nervous system (brain-tropic) display distinct molecular features. 13 Our study identified PLEKHA5, a gene involved in normal brain development, as a likely mediator of melanoma brain dissemination.…”
Section: Introductionmentioning
confidence: 99%